2019
DOI: 10.1002/eji.201948342
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of CreER transgenic mice for the study of brain macrophages: A case study

Abstract: Conditional mutagenesis and fate mapping have contributed considerably to our understanding of physiology and pathology. Specifically, Cre recombinase‐based approaches allow the definition of cell type‐specific contributions to disease development and of inter‐cellular communication circuits in respective animal models. Here we compared Cx3cr1CreER and Sall1CreER transgenic mice and their use to decipher the brain macrophage compartment as a showcase to discuss recent technological advances. Specifically, we h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 50 publications
3
52
0
Order By: Relevance
“…In the second study, Chappell‐Maor et al. not only confirm reporter leakiness as described in point 2 above, but also reiterate another concern with Cre/loxP systems; nonspecific and/or undesired targeting [16]. With some exceptions, Cre/CreER mouse strains are rarely uniquely specific to a single cell‐type.…”
Section: Figurementioning
confidence: 65%
See 1 more Smart Citation
“…In the second study, Chappell‐Maor et al. not only confirm reporter leakiness as described in point 2 above, but also reiterate another concern with Cre/loxP systems; nonspecific and/or undesired targeting [16]. With some exceptions, Cre/CreER mouse strains are rarely uniquely specific to a single cell‐type.…”
Section: Figurementioning
confidence: 65%
“…Previous articles have cast concerns on conditional mutagenesis, particularly the accuracy and efficiency of excision of different floxed alleles [11–14]. Expanding on this, this issue of the European Journal of Immunology features two elegantly designed and complementing studies, which provide an insight into the complexity of inducible gene targeting [15,16]. Both studies made use of two tamoxifen‐inducible CreER strains commonly used for manipulating brain macrophages; Cx3cr1 CreER and Sall1 CreER .…”
Section: Figurementioning
confidence: 99%
“…The same holds true for the Cx3cr1 CreERT2 strain, since it has been recently shown that Cx3cr1 Cre can drive rearrangements in neurons, most likely transiently during development . We also refer to the recent comprehensive analysis by the Jung group which describes complementary findings and shows via the RiboTag approach that Sall1 CreERT2 induces recombination in neurons and other glia . While the Cx3cr1 CreERT2 line did not induce recombination of the RiboTag allele in neurons , we cannot exclude leaky neuronal recombination for all other loxP flanked sequences, which will depend on the nature and size of the floxed allele.…”
mentioning
confidence: 68%
“…We also refer to the recent comprehensive analysis by the Jung group which describes complementary findings and shows via the RiboTag approach that Sall1 CreERT2 induces recombination in neurons and other glia . While the Cx3cr1 CreERT2 line did not induce recombination of the RiboTag allele in neurons , we cannot exclude leaky neuronal recombination for all other loxP flanked sequences, which will depend on the nature and size of the floxed allele. Finally, when using the Cx3cr1 CreERT2 strain to dissect the role of tissue‐resident versus recruited myeloid cells that infiltrate the brain during disease , it is advisable to confirm that leaky recombination is low in the latter population.…”
mentioning
confidence: 82%
“…Aside from Cx3CR1, knock-in GFP and CreER lines have been generated for the microglial-enriched transcription factor Sall1 (Buttgereit et al, 2016). However, significant caveats for these lines exist, including the fact that Sall1-GFP and CreER both disrupt the function of the Sall1 gene, and that Sall1-CreER marks a broad range of non-myeloid CNS cell types (Chappell-Maor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%